Pengaruh Kualitas Situs Web Dinas Kependudukan dan Pencatatan Sipil Kota Yogyakarta Terhadap Kepuasan Pengguna Masyarakat Kota Yogyakarta - Zulkarnain, Guntur Akhmad; Khuntari, Diana; Marwati, Arum (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
In the era of technological advancement, information system transformation affects public services, including those at the Population and Civil Registration Office (Dindukcapil) in Yogyakarta City. The Dindukcapil website plays an essential role in delivering information and administrative services; however, low ratings indicate user dissatisfaction. This study aims to assess the impact of the Dindukcapil website quality on user satisfaction in Yogyakarta, utilizing the Webqual 4.0 theory, which includes dimensions of usability quality, information quality, and service interaction quality, as well as user satisfaction theory covering expectation alignment, revisit intention, and recommendation availability. This research uniquely contributes by specifically examining the impact of Dindukcapil website quality on public service user satisfaction at the regional government level. A descriptive quantitative method using an online questionnaire was analyzed with SPSS version 26 through validity, reliability, classical assumption tests, simple linear regression, and T-tests. Results indicate that website quality positively and significantly influences user satisfaction by 54.4%, while 45.6% is affected by other variables. Based on the study’s findings, recommendations for Dindukcapil include evaluating and improving website content by enhancing SEO, user personalization, security, reputation, and providing a feedback section to strengthen engagement and address community aspirations.